The Ability of Class XII Students of The Islamic Boarding School of Syeikh Burhanuddin Kuntu in Understanding Meaning of Fi’il Tsulasi Mazid in The Book Ta'lim Al-Muta Aalım by Sheikh Burhanuddin Az-Zarnuji/ Istî’abu Ma’aniy al-‘Af’ali as-Tsulastiyah al-Mazidah fi Kitâbi Ta’lim al-Muta’allim li as-Syaikh Burhanuddin al-Zarnuji lada Talâmizi as-Shaffi at-Tsâni fi Ma’hadi Syaikh Burhanuddin Kuntu - Almuna Waro, Tri; Amrizal, Amrizal; Maulana, M. Faisal; Haqq, Muhammad Faliyyul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Islamic boarding school students who study qowaid sometimes have a very high level of memorization of qowaid, but their level of understanding in the practice of reading Arabic texts and the like is not capable, as evidenced when they are asked questions by their teachers when practicing reading the Turosh Book/Kitab Kuning/Kitab Gundul. This research aims to determine the level of ability of class By carrying out a test in the form of a question sheet which is given to test the students' understanding of the meaning of tsulasi mazid which has been learned from the practice of reading the book Ta'lim Al-Muta'aalim. This research uses descriptive qualitative research methods with data collection techniques in the form of tests on 20 selected class XII students and documentation. So after conducting the research, it was concluded that the level of understanding of the students in understanding the meaning of the mazid tsulasi in the book Ta'lim Al-Muta aalım by Sheikh Burhanuddin Az-Zarnuji was categorized as increasing along with continuous training. This is proven by the percentage of the first test to the third test from 0 % categorized as very good up to 20%, in the third test 55% were categorized as good, and 25% were categorized as quite good.